The cognitive behavioral counseling approach in the treatment of students addicted to on-line video games - Reyes, Isaias B. (2009)
The popularity of computer games stands out in contrast to the lack of understanding of computer games as an addictive activity which disables a student from performing his daily tasks. The investigation was done among first to fourth year high school students during the school year 2007-2008. Thirteen students were referred by their teachers because of low academic performance. All were found positive for addictive behavior associated with online gaming playing for more than two hours a day at three to four times a week. The students and their subject teachers accomplished survey questionnaires and participated in interviews. The students attended regular counseling sessions. The effectiveness of this technique was reflected in the improvement in attendance, tardiness and grades of the students in some subjects like EKAWP.